Measuring Sports’ Perceived Benefits and Aggression-Related Risks: Karate vs. Football - Limpo, Teresa; Tadrist, Sid (Frontiers in Psychology, 2021)
Little is known about people’s perceived benefits and risks of sports, despite their role in shaping people’s intentions to engage on them. Here, we developed and tested a scale to measure perceived physical, emotional, cognitive, and social benefits as well as aggression-related risks of karate and football. Additionally, we compared these perceptions within and between these two sports, as well as among undergraduates with current/former participation in different types of physical activity (viz., martial artists, team sports players, participants in other types of physical activity, and non-participants). After a literature review, we created a 5-factor scale with 20 items administered to 184 undergraduates, along with questions about physical activity participation. After removing five items, confirmatory factor analyses supported the factor structure of the scale. Factor loadings and reliability indices were acceptable, though less than desirable results were found concerning the average variance extracted of all benefits dimensions and the reliability of the social benefits dimension. Analyses of variance showed that: (a) physical benefits were seen as the salient outcomes of karate and football, though martial artists perceived karate’s physical, emotional, and social benefits to the same extent; (b) in comparison to football, karate was perceived to bring more emotional and cognitive benefits and to entail less aggressiveness risks; (c) karate and football perceptions varied as a function of participant’s involvement in physical activity. This study presents a promising instrument to gather information on people’s perceptions about karate and football, which can be used to foster people’s engagement in them.